Gender differences in the level of interactions between the physical activity and quality of life of 10 years old children - Monika Czaková; Jaroslav Broďani; Natália Dvořáčková (Matej Bel University, 2022)
This article deals about the interactions between a physical activity, joy of movement and quality of life of 10 years old boys and girls from Slovak primary schools. The PAQ, PACES and Children´s Worlds The International Survey of Children´s Well-Being (ISCWeB) surveys were used to obtain the data. The survey was attended by94 boys and 86 girls from primary schools. Statistical and practical significance of differences or relationships are assessed by the nonparametric methods (U, Z, r, rs,). Despite differentiated sports level of boys and girls, the extracurricular physical activity per week is on the same level. Girls prefer unorganized physical activity, which brings them joy. Higher summary score values are found in girls' side in the area of a home, family, friends, school, self-evaluation, orientation to their future, and their leisure time. Subjective evaluation of the material area has the boys and girls on the same level. Correlation analysis between defined factors confirmed the differentiated impact of extracurricular activities and the joy of movement on interactions with areas of quality of life of 10-year-old boys and girls. Boys show a higher frequency of positive interactions than girls. Higher closeness to areas of quality of life than the level of physical activity is demonstrated by the joy of movement. DOI: https://doi.org/10.24040/sjss.2021.7.2.64-73